Therapeutic Potential of a Vasopressin V2 Receptor Antagonist for Calcium Channel Blocker-Associated Edema with Vasospastic Angina - Kojiro Toda; Masashi Fujino; Kota Murai; Teruo Noguchi (Case Reports in Cardiology)
Calcium channel blocker- (CCB-) associated peripheral edema does not resolve without CCB discontinuation or dose reduction. However, renin–angiotensin system (RAS) inhibitors have been reported to be effective for CCB-associated edema. We report a case of vasospastic angina with refractory CCB-associated edema. A 78-year-old man had refractory edema induced by a CCB. It was successfully treated with tolvaptan, an active vasopressin V2 receptor antagonist. The aim of this case report is to understand the mechanism and treatment of CCB-associated peripheral edema and how tolvaptan affects peripheral edema.